Induction of triploidy in mrigal, Cirrhinus mrigala by thermal shock treatment of fertilized eggs - KarlMarx, K; Sukumaran, N; Rahman, Md. Kaleemur (Indian Journal of Fisheries, 2011)
Triploid mrigal, Cirrhinus mrigala was produced by thermal shock treatmentof eggs five minutes after in vitro fertilization. Cold shock at 12°C, 15°C, and18°C and heat shock at 40°C were used for the restoration of second polar body in the fertilized eggs. Heat shock for 1 minute duration appeared more effective. Induction of triploidy was confirmed by counting the chromosome number.